Contactless and robust dielectric microspheres-assisted surface-enhanced Raman scattering sensitivity improvement for anthrax biomarker detection - Ge, Mengyi; Zhao, Wenfeng; Han, Yue; Gai, Hongwei; Zong, Chenghua (Frontiers in Chemistry, 2022)
This report presents a contactless and robust dielectric microsphere (DM)-assisted SERS enhancement method to improve surface-enhanced Raman scattering (SERS) detection sensitivity. DMs that could focus and collect light were embedded within the PDMS film to avoid direct contact with the analytical solution and improve detection reliability. The as-prepared DMs-PDMS film was integrated with a microfluidic technique to enhance the SERS signal of a liquid substrate. Detection in microfluidic systems can reduce reagent consumption, shorten assay time, and avoid evaporation of the colloid substrate solution. The robustness and potential influencing factors of DMs-PDMS film-assisted SERS enhancement (DERS) were evaluated using 4-aminothiophenol (4-ATP) as the Raman probe. The sensing performance of the proposed method toward dipicolinic acid (DPA) was evaluated, and an evident signal intensification was obtained. Remarkably, the DMs-PDMS film can also be implemented on solid substrates. A proof-of-concept experiment was performed by covering the DMs-PDMS film directly over an AgNPs@Si solid substrate wherein a 5.7-fold sensitivity improvement was achieved.